Stressors, coping, and well-being among sports coaches: A systematic review - Norris, L. A.; Didymus, F. F.; Kaiseler, M. (Psychology of Sport and Exercise, 2017)
Objectives: Sports coaching can be an inherently stressful occupation because coaches must fulfill multiple roles and cope with various expectations. Further, stress and well-being have implications for coach performance. The objective of this study was, therefore, to conduct a systematic review of literature on stressors, coping, and well-being among sports coaches. Design: A systematic review using PRIMSA guidelines. Method: Thorough and systematic literature searches of PsycINFO, SPORTDiscus, and Web of Science were conducted. To be eligible for inclusion, papers had to be published in the English language between January 1994 and March 2016 and as full papers in peer-reviewed journals. Results: The final sample consisted of 38 studies that were conducted with 4188 sports coaches. This sample consisted of 19 qualitative, 17 quantitative, and two mixed methods studies. The findings demonstrate that coaches experience a variety of stressors relating to their performance and that of the athletes they work with in addition to organizational, contextual, interpersonal, and intrapersonal stressors. The findings also highlight that coaches use a variety of coping strategies (e.g., problem solving, social support, escaping the stressful environment) to reduce the negative outcomes of stress. Five studies that were included in this review focused on coaches` well-being and found that basic psychological needs satisfaction, lack of basic psychological needs thwarting, and self-determined motivation are needed for coaches to be psychologically well. Conclusion: Future research should address gaps in extant literature by using longitudinal study designs to explore coaches` appraisals of stressors, coping effectiveness, social support, and well-being among the unique sports coaching population.